Agromorphological characterization of traditional Spanish sweet cherry (Prunus avium L.), sour cherry (Prunus cerasus L.) and duke cherry (Prunus Xgondouinii Rehd.) cultivars - Perez Sanchez, R.=700 1 Gomez Sanchez, M.A.; Morales Cort, R.
(Es, En)
Ilus., 28 ref.
Keywords: PRUNUS AVIUM; PRUNUS CERASUS; RECURSOS GENETICOS; CONSERVACION DE LOS RECURSOS; ESPECIES EN PELIGRO DE EXTINCION; ANATOMIA DE LA PLANTA; PARAMETROS GENETICOS; FRUTO; ESPAÑA; CEREZA; HOMONIMIAS; SININIMIAS